2016
DOI: 10.1038/srep34232
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of the IFT-B cilia core complex due to mutations in IFT81 causes a Spectrum of Short-Rib Polydactyly Syndrome

Abstract: Short-rib polydactyly syndromes (SRPS) and Asphyxiating thoracic dystrophy (ATD) or Jeune Syndrome are recessively inherited skeletal ciliopathies characterized by profound skeletal abnormalities and are frequently associated with polydactyly and multiorgan system involvement. SRPS are produced by mutations in genes that participate in the formation and function of primary cilia and usually result from disruption of retrograde intraflagellar (IFT) transport of the cilium. Herein we describe a new spectrum of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 60 publications
(76 reference statements)
3
40
0
Order By: Relevance
“…The data also establish the molecular basis of SRPS type IV and demonstrate that it is allelic with SRPS type II. Previous publications of SRPS and ATD cases from the ISDR have included 22 additional families with mutations in nine ciliary genes ( DYNC2H1, WDR34, IFT52, ICK, INTU, IFT81, DYNC2LI1, IFT43 , and WDR35 ), including six genes not represented among the current set of families (Duran, et al., ; Huber et al., ; Taylor et al., ; Taylor et al., ; Toriyama et al., ; Zhang et al., ). Mutations have also been reported in families in this spectrum of disease in six additional genes, C21ORF2 (McInerney‐Leo et al., ; Wheway et al., ), TCTEX1D2 (Gholkar et al., ), IFT172 (Halbritter et al., ), KIAA0586 (Alby et al., ), CEP120 (Shaheen et al., ), or IFT122 (Walczak‐Sztulpa et al., ), bringing the number of known skeletal ciliopathy genes to twenty six.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data also establish the molecular basis of SRPS type IV and demonstrate that it is allelic with SRPS type II. Previous publications of SRPS and ATD cases from the ISDR have included 22 additional families with mutations in nine ciliary genes ( DYNC2H1, WDR34, IFT52, ICK, INTU, IFT81, DYNC2LI1, IFT43 , and WDR35 ), including six genes not represented among the current set of families (Duran, et al., ; Huber et al., ; Taylor et al., ; Taylor et al., ; Toriyama et al., ; Zhang et al., ). Mutations have also been reported in families in this spectrum of disease in six additional genes, C21ORF2 (McInerney‐Leo et al., ; Wheway et al., ), TCTEX1D2 (Gholkar et al., ), IFT172 (Halbritter et al., ), KIAA0586 (Alby et al., ), CEP120 (Shaheen et al., ), or IFT122 (Walczak‐Sztulpa et al., ), bringing the number of known skeletal ciliopathy genes to twenty six.…”
Section: Discussionmentioning
confidence: 99%
“…We identified causal variants in only six out of 152 families and only two of the 14 genes ( TRAF3IP1 and IFT80 ) that encode IFT‐B components. In the total ISDR skeletal ciliopathy cohort, there was also one family with unclassified SRPS due to IFT52 mutations (Zhang et al., ) and one family each with ATD and SRPS type III due to IFT81 mutations (Duran, et al., ), so overall nine out of 175 (5%) families studied had IFT‐B defects. It is unclear why the genes encoding anterograde IFT components are less frequently mutated than retrograde molecules in the SRPS‐ATD spectrum of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no patient mutations in IFT22 have been reported to date, a recent study identified a series of mutations in IFT81 causing Short-Rib Polydactyly Syndrome (SRPS) (Duran et al, 2016). One of the disease mutations reported was an in-frame deletion of amino acid L435, which corresponds to L443 in trypanosomes and is a well-conserved residue positioned directly in the interaction interface with IFT22 (Appendix Fig S7).…”
Section: Ift81 Short-rib Polydactyly Syndrome Mutation May Affect Iftmentioning
confidence: 99%